Cross-Sectional Study of Occlusal Loading and Periodontal Status of Teeth with Deflective Occlusal Contacts - Ximena Anca Nicolae; Elena Preoteasa; Catalina Murariu Magureanu; Cristina Teodora Preoteasa (Bioengineering, 2025)
Aim: To evaluate whether maximum occlusal loading and periodontal status are different between teeth presenting deflective occlusal contacts and those without such contacts, specifically adjacent and homologous teeth. Method: A cross-sectional study was conducted using OccluSense to detect deflective contacts and quantify occlusal load per tooth. For group comparisons, the Kruskal–Wallis, Friedman, Cochran’s Q, and chi-squared tests were used. Results: A total of 493 teeth with deflective contacts were compared to 473 adjacent (first control group) and 457 homologous teeth (second control group). Teeth with deflective contacts showed significantly higher occlusal loading (mean value: 208) than adjacent (72) and homologous teeth (97) (p < 0.05). They also exhibited more advanced periodontal damage, including deeper probing depths, greater gingival recession, alveolar bone loss, and a wider periodontal ligament space. Deflective contacts in centric relation were more strongly linked to periodontal deterioration than those in protrusive or lateral mandibular movements, despite similar occlusal forces. Conclusions: Within this study’s limitations, deflective occlusal contacts are associated with increased occlusal forces and more severe periodontal damage, suggesting a biomechanical factor in periodontal disease progression.